Specific haplotypes of the RET proto-oncogene are over-represented in patients with sporadic papillary thyroid carcinoma. Issue 4 (1st April 2002) - Lesueur, F; Corbex, M; McKay, J D; Lima, J; Soares, P; Griseri, P; Burgess, J; Ceccherini, I; Landolfi, S; Papotti, M; Amorim, A; Goldgar, D E; et al.
Abstract : Background: Papillary thyroid carcinoma (PTC), which may be sporadic (95%) or familial (5%), has a prevalence adjusted for age in the general population of 1:100 000. Somatic rearrangements of the RET proto-oncogene are present in up to 66% of sporadic tumours, while they are rarely found in familial cases. Purpose: In order to determine if some variants of this gene, or a combination of them, might predispose to PTC, we looked for an association of RET haplotype(s) in PTC cases and in controls from four countries matched for sex, age, and population. Methods: Four single nucleotide polymorphisms (SNPs) across the RET coding sequence were typed and haplotype frequencies were estimated. Genotype and haplotype distributions were compared among these cases and controls. Results: Ten haplotypes were observed, the seven most frequent of which have been previously described in sporadic Hirschsprung patients and controls. The single locus analyses suggested association of exon 2 and exon 13 SNPs with sporadic PTC. The haplotype analysis showed over-representation of one haplotype in French and Italian sporadic PTC, whereas a different haplotype was significantly under-represented in French familial PTC. Conclusions: Our data suggest that some variants of RET and some specific haplotypes may act as low penetrance alleles in the predisposition to PTC.